Chemistry, pharmacology, uses, safety studies, and clinical studies of glucosyl hesperidin: An overview - Eric Wei Chiang Chan, Siu Kuin Wong, Hung Tuck Chan (Journal of Applied Pharmaceutical Science, 2025)
Glycosyl hesperidin (GH) or hesperetin rutinoside has been patented in 1997 and 2000, and has been endorsed as a novel food in 2024. A flavanone mostly from Citrus fruits, GH can be synthesized by adding one glucose molecule to hesperidin. Pharmacological properties of GH are diverse with anti-hypertension, antimicrobial, anti-inflammatory, and anti-obesity being the major activities. Food additives, functional food, beverage, health supplement, and cosmetics are some of the uses of GH. Now a commercial product, GH is being sold in Japan, Taiwan, and Korea as a dietary supplement. From 2004 to 2023, a total of 13 clinical studies involving GH were reported in the literature. All conducted in Japan, their area of study included arthritis, triglyceride, blood flow, obesity, lower leg swelling, vasodilation, vascular flexibility, and hepatic function. In the concluding remarks, the prospects and fields for further research of GH are suggested.
Keywords: G-hesperidin, Citrus fruits, flavanone, hesperidin, food supplements